Power to the Transfer : Critical Race Theory and a Transfer Receptive Culture - Jain, Dimpal; Herrera, Alfred R.; Bernal Melendez, Santiago N. (Book collections on Project MUSE., 2020)
"This book engages history, theory, and current events to help examine the historical and contemporary relationship between community colleges and universities as it pertains the support and success of transfer students of color. Currently U.S. community colleges serve nearly half of all students of color in higher education who for a multitude of reasons do not continue their education by transferring to a university or college. For those who do transfer, often the responsibility for retention, graduation, and overall success is placed on the student rather than the institution. The goal of this book is to provide direction towards the development and maintenance of a transfer receptive culture which is defined as an institutional commitment by a university to support transfer students of color. A transfer receptive culture explicitly acknowledges the role of race and racism in the vertical transfer process from a community college to a university and unapologetically centers transfer as a form of educational equity in the higher education pipeline"--